STUDY ON MORPHO-PHYSICAL FLORAL CHARACTERS OF MANGO (MANGIFERA INDICA) VARIETIES IN SARLAHI, NEPAL - Kiran Thapa; Pawan Pyakurel; Poojan Adhikari; Susma Adhikari; Kabita Bhat; Abishek Shrestha; Rupesh Chaudharuy (Science Heritage Journal)
Floral characteristics of 27 mango varieties were studied during February-May, 2024. Distinct variations were found among the studied varieties. Significant variation were observed in term of number of male flower per inflorescence, number of hermaphrodite flower per inflorescence, length of inflorescence and width of inflorescence ranging from 57 to 1737, 7 to 461, 19 cm to 40.6 cm, 6.4 cm to 25.7 cm respectively. The result disclosed that in all varieties flowers were of pentamerous type and inflorescence position were found terminal. The number of male flower per inflorescence were highest in Bombay (1737). In term of number of hermaphrodite flowers per inflorescence, chausa has highest number (461). In overall, male flower per inflorescence were more than hermaphrodite flower per inflorescence across all varieties except Amrapali, Jarda and Chausa. Ratna has the longest inflorescence (40.6 cm) and widest inflorescence (25.7 cm). From the study, it can be inferred that chausa will have more fruit set as it has more hermaphrodite flowers but seeing the overall floral character Ratna is more superior as it has longest and widest inflorescence and second highest in term of number of hermaphrodite flower among the studied varieties. The findings of the study will be beneficial for breeding purposes while developing new varieties of superior quality.